Post-buckling behaviors of a spinning composite thin-walled pipe conveying fluid considering thermal effects - Qin, Ying; Lv, Haiwei; Zhang, Xuanling; Li, Xiao (Ocean engineering, 2025)
For some fluid-conveying pipes with spinning motion, buckling is a necessary subject owing to the post-buckling deformation and vibration caused by the pressure at the end of the pipes under some complex working conditions such as improper pipeline design, pipeline aging, temperature change, etc. To understand the post-buckling behaviors of the pipes, this work proposes a mathematical model for the post-buckling static deformation and post-buckling vibration of a spinning composite thin-walled beam conveying fluid under thermal effects. The out-of-plane warping deformation and von Kármán geometric nonlinearity are considered to model the beam, and the nonlinear equations of extension-bending coupled motion are established using Hamilton's principle. Afterwards, the generalized differential quadrature method (GDQM) and pseudo arclength continuation technique are adopted to obtain the post-buckling paths and vibration characteristics around the buckled configuration. The influence mechanisms of spinning angular velocity, fluid velocity and design parameters on the post-buckling behaviors with the coupled motion is paid to special attention, and the mode veering phenomenon of the coupled vibration in the post-buckling domain is also detected. Results show that the static displacement, vibration frequency and mode shape in post-buckling domain exhibit a prominent change with the effects of spinning motion and conveying fluid. •A gratifying mathematical model for post-buckling coupled vibration is proposed.•The model considers both spinning motion and internal axial flow.•The post-buckling paths and coupled vibration in the post-buckling domain are studied.•Mode veering phenomenon is detected which can provide guidance for internal resonance.•The mechanism how the spin and axial flow affect post-buckling behaviors is explored.